Word formation process of terms in COVID-19 pandemic - Tira Nur Fitria (University of Muhammadiyah Purwokerto, 2021)
The objectives of this research are to know the type and examples of the word-formation process of the terms that appear during pandemic Covid-19. This research uses qualitative research. From the result analysis, some types of word-formation processes include borrowing, compounding, blending, acronym, clipping, and multiple processes. In borrowing, for example, the words “Rapid test” and “Swab test”. In compounding, for example, the words “handsanitizer, lockdown, coronacoma, coronaspeck and self-quarantine”. In blending, for example, the words ‘covid, covidiot, covidient, quarantini, infodemic, quaranteam, coronials, covexit, covidivorce, quaranteen and coroncation”. In clipping, for example, the words ‘sanny” and “iso”. The word “sanny’ comes from “hand sanitizer” and “Iso” comes from “isolation”. In the acronym, for example, the initials WFH (Work from Home), PPE (Personal Protective Equipment), WFO (Work from Office), and PUI (Person Under Investigation). In multiple processes for example the words “handwashing”, zoomboombing, coronababies, self-isolation”.